Delayed revascularization in acute ischemic stroke patients - Eastin, T. Marc; Dye, Justin A.; Pillai, Promod; Lopez-Gonzalez, Miguel A.; Huang, Lei; Zhang, John H.; Boling, Warren W. (Frontiers in Pharmacology, 2023)
Stroke shares a significant burden of global mortality and disability. A significant decline in the quality of life is attributed to the so-called post-stroke cognitive impairment including mild to severe cognitive alterations, dementia, and functional disability. Currently, only two clinical interventions including pharmacological and mechanical thrombolysis are advised for successful revascularization of the occluded vessel. However, their therapeutic effect is limited to the acute phase of stroke onset only. This often results in the exclusion of a significant number of patients who are unable to reach within the therapeutic window. Advances in neuroimaging technologies have allowed better assessment of salvageable penumbra and occluded vessel status. Improvement in diagnostic tools and the advent of intravascular interventional devices such as stent retrievers have expanded the potential revascularization window. Clinical studies have demonstrated positive outcomes of delayed revascularization beyond the recommended therapeutic window. This review will discuss the current understanding of ischemic stroke, the latest revascularization doctrine, and evidence from clinical studies regarding effective delayed revascularization in ischemic stroke.